Factors Related to Nurses Caring Behavior in Inpatient Unit - Fitriani, Rina; Wihardja, Hany (Journal of Nursing Care, 2024)
Caring is the essence of nursing practice. Caring is also an approach to increase a sense of caring for patients. This attitude can help patients achieve improved quality of recovery and health. Caring from the patient's point of view is a humane attitude expected by the patient. Caring is basically a nurse's behavior, so that caring basically depends on the characteristics and motivation of an individual nurse. This study aims to identify the factors that most influence the caring behavior of nurses in the inpatient room. Research methodology: This research is an analytic observational study with a Cross-sectional approach. The samples technique was total population of nurses that is 137 nurses. Three instrument used in this study : characteristic respondent, work motivation, Caring Nurse-Patient Interaction Scale (CNPI-23). Data analysis using Chi Square test, Kendall's Tau-b and Logistic Regression. The results of this study found that nurses' work motivation was the most influencing factor for nurses' caring behavior (p value 0.022).  Nurses with high work motivation voluntarily perform their best efforts and skills when working and do not feel physical or mental pressure. As a result, they can show a sense of caring, empathy, and sensitivity to patients during nursing care. Further recommendation that can be given to hospital management are to pay attention to the creation of a motivational work climate, so that workers have high work motivation at work.